Enhanced Photoconductivity at Dislocations in SrTiO3. Issue 32 (10th July 2022) - Kissel, Maximilian; Porz, Lukas; Frömling, Till; Nakamura, Atsutomo; Rödel, Jürgen; Alexe, Marin
Abstract: Dislocations are 1D crystallographic line defects and are usually seen as detrimental to the functional properties of classic semiconductors. It is shown here that this not necessarily accounts for oxide semiconductors in which dislocations are capable of boosting the photoconductivity. Strontium titanate single crystals are controllably deformed to generate a high density of ordered dislocations of two slip systems possessing different mesoscopic arrangements. For both slip systems, nanoscale conductive atomic force microscope investigations reveal a strong enhancement of the photoconductivity around the dislocation cores. Macroscopic in‐plane measurements indicate that the two dislocation systems result in different global photoconductivity behavior despite the similar local enhancement. Depending on the arrangement, the global photoresponse can be increased by orders of magnitude. Additionally, indications for a bulk photovoltaic effect enabled by dislocation‐surrounding strain fields are observed for the first time. This proves that dislocations in oxide semiconductors can be of large interest for tailoring photoelectric functionalities. Direct evidence that electronic transport is confined to the dislocation core points to a new emerging research field. Abstract : Dislocations can boost the photoconductivity in oxide semiconductors. Well‐ordered, high‐density dislocation arrays dedicatedly produced in Fe‐doped SrTiO3 single crystals show manyfold increased photoconductivity in the regions around dislocation compared to the dislocation free regions of the sample.